Ethnobotanical survey on plants used as traditional salad food (ulam) in Kampung Taun Gusi, Kota Belud Sabah, Malaysia - Awang-Kanak, Fadzilah; Abu Bakar, Mohd Fadzelly; Mohamed, Maryati (2017)
A preliminary ethnobotanical survey of traditional salad food or ulam was conducted within Sama–Bajau community in Kampung Taun Gusi, Kota Belud Sabah, Malaysia on May 2017.Three key informants were selected using snowball sampling technique, and data about traditional salad food (ulam) were collected by semi-structured interview and field observation. A total of 28 species of plants from 26 genera and 20 families were recorded have been consumed as ulam. The study also reveals apart from being consumed as traditional salad food (ulam), 15 species are also used as herbal medicine to treat or prevent various diseases such as cough, diabetes, high blood pressure, cancer, flu, fever, red eyes, ringworms, and for postpartum treatment. Zingiberaceae is the most utilized plant as an herbal medicine by Sama-Bajau community of Kampung Taun Gusi, Kota Belud. These Zingiberaceae species are namely; Curcuma caesia (kunyit hitam), Curcuma zanthorrhiza, (temulawak), and Zingiber zerumbet (lempoyang). Clinacanthus nutans (belalai gajah), and Orthosiphon stamineus (misai kucing) are recorded to be used as herbal medicine to treat diabetes and high blood pressure. The decoction of the young shoot of Capsicum annum (lada) has been used to treat ringworms among children and red eyes, moreover, the paste of the leaf has been used to reduce high fever. Meanwhile, Cosmos caudatus (ransa ransa) and Centella asiatica (pegaga) have been consumed for health and wellness maintenance and as anti-aging herbs.